RESPON PAKAN HIJAUAN DAN DEDAK PADI TERHADAP PERTUMBUHAN RANGGAH RUSATIMOR (Rusa Timorensis) DI PENANGKARAN DRAMAGA BOGOR - Poetri, Eko (AgriSains, 2014)
The research aims to determine the influence of rice bran and forage given to growth of male Timorensis deer. Four head deer used with a range of the age 4 – 10 year and body weight of 30 – 70 kg. The Latin Square Design was implemented with four treatment and four replication. The treatment were P0 = forage without rice bran  (control), P1 = forage + 150 g of rice bran, P2 = forage + 300 g of rice bran, and P3 = forage + 450 g of rice bran. Forage used as basal rations was Gajah Grass (Pennisetum purpureum), Sulanjono (Herochloe horsfieldii Max.), Kaliandra (Calliandra calothyrsus Meisn) and Gewor (Comellina mudiflora L.).  The four forage were added by rice bran as concentrate. The forage was given as many as 10 % x body weight x 2. The research was carried out  for 60 days  divided into 4 (four) periods, each of them consisting of a preliminary period of five days followed by 10 days of data collection. The parameter were feed measurement, morfometric measurement of deer, body weight of Timorensis deer. The result showed that given forage added by rice bran 450 g (P3) significantly influencedto the growth of of maleTimorensis deer, with growth range of 1.55 cm/day. Keywords : Timorensis deer, forage, growth, rice bran